Recovery and Regeneration of Spent Lithium-Ion Batteries From New Energy Vehicles - Zhao, Qing; Hu, Lv; Li, Wenjie; Liu, Chengjun; Jiang, Maofa; Shi, Junjie (Frontiers in Chemistry, 2020)
As a result of the rapid growth of new energy vehicles markets, the output of spent lithium-ion batteries (LIBs) has shown an explosive growth. It's of great economic, environmental and social benefits to realize harmless treatment and resource utilization spent LIBs, which contain a large proportion of valuable metal elements (e.g., Li, Ni, Co, Mn, Cu and Al) and poisonous chemicals (e.g., lithium hexafluorophosphate and polyvinylidene fluoride). The present work summarized the leading technologies and hot issues in the disposal of spent LIBs from new energy vehicles. With particular attentions to the recovery and regeneration technologies for electrode materials. Finally, the development trend of innovative technologies for the recycling of spent LIBs is further recommended.